Production of mouse anti-CD4 antibodies by DNA-based immunization - Kasinrerk W. (2014)
The intramuscular injection of plasmid DNA encoding an antigenic protein has been developed recently as a tool for immunization. DNA-based immunization was shown to generate immune responses against the encoded antigen in diverse animal species. In this report, we present the use of DNA-based immunization for the production of antibodies to CD4, a human leukocyte surface molecule. Mice were injected intramuscularly with eukaryotic expression vector containing cDNA encoding CD4 protein, termed CD4-DNA, and were subsequently assayed for anti-CD4 antibody production by indirect immunofluorescence. Sera collected from 2 of 3 inoculated mice reacted with CD4 expressing transfected COS cells and Sup-T1 cells. Anti-CD4 antibody activity was abolished by adsorption with CD4 molecule expressing cells. CD4+ cell depleted lymphocytes were also used to confirm the specificity of the anti CD4 antibodies present in immune serum. CD4-DNA immune serum reacted with approximately 1/3 of freshly isolated lymphocytes but to very few cells in the CD4+ cells-depleted preparation. CD4-DNA immunized sera was used to enumerate CD4+ cells in the peripheral blood of 6 healthy donors and 2 AIDS patients. The number of CD4+ cells estimated by DNA immunized sera was very similar to estimates using standard anti-CD4 monoclonal antibody Leu3a. DNA-based immunization is therefore capable of raising antibodies to human leukocyte surface antigens. This technology may be useful for producing antibodies to other cell surface antigens in mice or other animals.